Ankle fractures with syndesmotic stabilisation are associated with a high rate of secondary osteoarthritis. Issue 2 (April 2019) - Ray, Robbie; Koohnejad, Nina; Clement, Nick D.; Keenan, Gary F.
Highlights: The authors evaluated 120 ankle fractures with syndesmotic injuries with upto 8 years follow up. 13 patients (11%) developed clinically significant osteoarthritis (cOA) of the ankle. Independent predictors of cOA of the ankle were increasing age and radiographic malreduction of the syndesmosis. Care should be taken to ensure radiographic reduction of the syndesmosis and open reduction should be considered in cases where anatomical reduction is uncertain. Abstract: Background: The primary aim of this study was to present the incidence of clinically significant end stage osteoarthritis (cOA) after syndesmotic fixation of ankle fractures. The secondary aim was to and identify independent predictors of cOA. Methods: A retrospective review of consecutive patients presenting to a single University affiliated institution between March 2008 and May 2010 was undertaken. Inclusion criteria were ankle fractures with syndesmotic stabilisation. Patients were excluded if pre or postoperative radiographs were missing or were lost to follow up. Data were gathered regarding demographics, fracture pattern, fixation methods, reduction parameters, screw removal, revision surgery, complications and cOA up to seven years post injury. Results: Data were available for 120 patients (86%). In total, 13 patients (11%) developed cOA. Univariate analysis showed that increasing age, open fracture, malreduction of the syndesmosis, removal of symptomatic screws, revision surgery and complications were predictors of developing cOA. Cox regression analysis revealed increasing age (hazard ratio (HR) 1.09, p = 0.006), and malreduction (HR 45.5, p = 0.001) were independent predictors of developing cOA. Conclusions: Ankle fractures with syndesmotic stabilisation represent a severe injury with a high rate of cOA. The only modifiable risk factor for developing cOA in this large series of patients was radiological malalignment. When syndesmotic stabilisation is required, careful intraoperative assessment should be undertaken to ensure the syndesmosis is reduced.